Fashion Design Based on Baduy Culture: The Fusion of Essentiality, Spirituality, and Exploration in Seba Baduy 2024 - Ardita Ayulestari Soemardi; Tetes Annisa Lestari; Rizki Maulana Rachman; Annurul Annurul (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Seba Baduy is a series of events held annually as a tradition as a form of gratitude and a symbol of harmonious relations between humans, nature, and ancestors. This study aims to identify Baduy cultural elements that are integrated into fashion design works and analyze the values ​​of essentiality, spirituality, and exploration in these fashion designs with a blend of local Baduy culture. The research method used is qualitative, with data collection methods through literature studies and observations regarding Baduy culture, especially Baduy weaving and batik. This Baduy culture is collaborated with a more modern style, with the theme of Essentiality, Spirituality, and Exploration, which is related to simplicity and the elevation of local traditions. The final result of this research is a design titled "Sawarga," inspired by the Baduy tribe's house as a spiritual place, elaborated with traditional Baduy fabrics, packaged in a modern form. The values ​​of essentiality, spirituality, and exploration are reflected in the design, through the use of natural materials, silhouettes, and exploration of textile materials.